The Power of a Pledge Agreement Made Under Circumstances of Force - Aslan Noor; Herlin Nurdiani; Raisa Sari; Tasya Dania Azzahra (Universitas Trunodjoyo Madura, 2024)
To borrow or lend money is one example of an economic and financial transaction that often involves a contractual agreement. Collateral is an object that the debtor (borrower) gives to the creditor (lender) in exchange for a loan.